Wild houses - Barrett, Colin, 1982- (Grove Press, an imprint of Grove Atlantic, 2024)
"The riotous, raucous, and deeply resonant debut novel from "one of the best story writers in the English language today" (Financial Times), Wild Houses follows two outsiders caught in the crosshairs of a small-town revenge kidnapping gone awry. With his acclaimed and award-winning collections Young Skins and Homesickness Colin Barrett cemented his reputation as one of contemporary Irish literature's most daring stylists. Praised by Oprah Daily as "a doyen of the sentence," and by the Los Angeles Times as a writer of "unique genius," Barrett now expands his canvas with a debut novel that contains as much grit, plot, and linguistic energy as any of his celebrated short stories. As Ballina prepares for its biggest weekend of the year, introspective loner Dev answers his door on Friday night to find Doll English-younger brother of small-time local dealer Cillian English-bruised and in the clutches of Gabe and Sketch Ferdia, County Mayo's fraternal enforcers and Dev's cousins. Dev's quiet homelife is upturned as he is quickly and unwillingly drawn headlong into the Ferdias' frenetic revenge plot against Cillian. Meanwhile, Doll's girlfriend, seventeen-year-old Nicky, reeling from a fractious Friday and plagued by ghosts and tragedy of her own, sets out on a feverish mission to save Doll, even as she questions her future in Ballina. Set against Barrett's trademark depictions of small-town Irish life, Wild Houses is a thrillingly told story of two outsiders striving to find themselves as their worlds collapse in chaos and violence"--